International personnel policies and practices - Reymond, Henri (Praeger, 1985)
This volume presents a comprehensive critical analysis of the personnel policies and the administration of international organizations, in particular the UN. Reymond and Mailick take an in-depth look at the nature of the UN secretariat, the concept of international loyalty, recruitment, salaries, promotions, staff attitudes & motivations.